AtFH14 crosslinks actin filaments and microtubules in different manners. (1st February 2021) - Du, Pingzhou; Wang, Jiaojiao; He, Yunqiu; Zhang, Sha; Hu, Bailing; Xue, Xiuhua; Miao, Long; Ren, Haiyun
Abstract : Background Information: In many cellular processes including cell division, the synergistic dynamics of actin filaments and microtubules play vital roles. However, the regulatory mechanisms of these synergistic dynamics are not fully understood. Proteins such as formins are involved in actin filament–microtubule interactions and Arabidopsis thaliana formin 14 (AtFH14) may function as a crosslinker between actin filaments and microtubules in cell division, but the molecular mechanism underlying such crosslinking remains unclear. Results: Without microtubules, formin homology (FH) 1/FH2 of AtFH14 nucleated actin polymerisation from actin monomers and capped the barbed end of actin filaments. However, in the presence of microtubules, quantitative analysis showed that the binding affinity of AtFH14 FH1FH2 to microtubules was higher than that to actin filaments. Moreover, microtubule‐bound AtFH14 FH1FH2 neither nucleated actin polymerisation nor inhibited barbed end elongation. In contrast, tubulin did not affect AtFH14 FH1FH2 to nucleate actin polymerisation and inhibit barbed end elongation. Nevertheless, microtubule‐bound AtFH14 FH1FH2 bound actin filaments and the bound actin filaments slid and elongated along the microtubules or elongated away from the microtubules, which induced bundling or crosslinking of actin filaments and microtubules. Pharmacological analyses indicated that AtFH14 FH1FH2 promoted crosslinking of actin filaments and microtubules in vivo . Additionally, co‐sedimentation and fluorescent dye‐labelling experiments of AtFH14 FH2‐truncated proteins in vitro revealed the essential motifs of bundling actin filaments or microtubules, which were 63–92 aa and 42–62 aa in the AtFH14 FH2 N‐terminal, respectively, and 42–62 aa was the essential motif to crosslink actin filaments and microtubules. Conclusions and Significance: Our results aid in explaining how AtFH14 functions as a crosslinker between actin filaments and microtubules to regulate their dynamics via different manners during cell division. They also facilitate further understanding of the molecular mechanisms of the interactions between actin filaments and microtubules. Abstract : Research article : In this study, Du et al. found that AtFH14 prefers to bind and bundle microtubules than actin filaments. The microtubules‐bound AtFH14 as a crosslinker recruits actin filaments to microtubules through AtFH14's side‐binding activity, resulting in actin filaments to slide and elongate along or elongate away from the microtubules. The essential motifs of AtFH14 in bundling microtubules and actin filaments and in crosslinking them are further identified. Thus, these studies provide a novel mechanism for the synergistic dynamics between microtubules and actin cytoskeletons.